2018
DOI: 10.1093/rheumatology/key088
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms, pain and disability for adolescent patients with juvenile idiopathic arthritis: results from the Childhood Arthritis Prospective Study

Abstract: ObjectivesTo determine if depressive symptoms assessed near diagnosis associate with future measures of pain, disability and disease for adolescent patients diagnosed with JIA.MethodsData were analysed from JIA patients aged 11–16 years recruited to the Childhood Arthritis Prospective Study, a UK-based inception cohort of childhood-onset arthritis. Depressive symptoms (using the Mood and Feelings Questionnaire; MFQ), active and limited joint count, disability score (Childhood Health Assessment Questionnaire), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
54
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 42 publications
16
54
0
3
Order By: Relevance
“…[24][25][26][27][28][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] JIA subtype was described in 14 studies: 13 included polyarticular, [24][25][26]30,31,[35][36][37][38][39][40]45,46 11 included oligoarticular, 24,26,30,31,[35][36][37][38][39][40]46 10 included systemic, 25,26,30,31,[35][36][37][38]…”
Section: Population Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…[24][25][26][27][28][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] JIA subtype was described in 14 studies: 13 included polyarticular, [24][25][26]30,31,[35][36][37][38][39][40]45,46 11 included oligoarticular, 24,26,30,31,[35][36][37][38][39][40]46 10 included systemic, 25,26,30,31,[35][36][37][38]…”
Section: Population Characteristicsmentioning
confidence: 99%
“…Most studies that used validated screens for depressive symptoms reported prevalences of clinically significant symptoms in the range of 7-36% in children with JIA. [23][24][25][26]28,29,35,38,39,41,46,47 Reda et al used the MINI-KID psychiatric interview and reported that 93% of the patients had dysthymic disorder while 3% had major depressive disorder. 30 El Najjar et al found that all JIA patients scored above the cut-off for clinically significant symptoms on the CES-DC questionnaire.…”
Section: Prevalence Of Depressive Symptoms In Jiamentioning
confidence: 99%
See 1 more Smart Citation
“…Juvenile idiopathic arthritis (JIA) is the most common chronic acquired arthritis in children (Petty et al, ). The disease can impair both physical and psychosocial functions, resulting in developmental delays and chronic disability (Hanns et al, ; Magni‐Manzoni et al, ; Moorthy, Peterson, Hassett, & Lehman, ; Tollisen et al, ). Furthermore, emotional and school difficulties are major concerns in children with JIA (Bomba et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic diseases tend to increase the risk for depressive symptoms, this was also shown in JIA, when actively screening for depressive symptoms (21). Chronic diseases tend to increase the risk for depressive symptoms, this was also shown in JIA, when actively screening for depressive symptoms (21).…”
Section: Discussionmentioning
confidence: 78%